Legal and Social Foundations of the Resocialization Institute: The Experience of Ukraine and Foreign Countries - Ivchuk, Yu. Yu.; Pavlichenko, V.; Zhuravel, V. I.; Kovalenko, K. V.; Коваленко, К. В.; Zhuravel, V.; Havrylyuk, V. O.; Havrylyuk, V. (Novum Jus. – 2023. – Vol. 17, № 2. – P. 43-68, 2022)
Исправление и ресоциализация осужденного рассматриваются как процессы позитивных изменений, происходящих в его самой личности и создающих готовность к самостоятельному послушному поведению, а также возвращению осужденного к самостоятельной и общепринятой социально-нормативной жизни в обществе, то есть успешная реинтеграция в общество после освобождения и лишения криминального мировоззрения. Это остается одним из важнейших вопросов, обсуждаемых учеными для определения наилучшего пути достижения целей исправления и реабилитации бывших правонарушителей. Кроме того, ресоциализация имеет принципиальное значение для решения широкого круга социальных и социально-практических задач, не только для профилактики и искоренения преступности, но и для профилактики социальных девиаций в целом. Поскольку реинтеграция преступников в общество является актуальной социальной проблемой, подробный анализ процесса ресоциализации преступников имеет практическое значение. Методологической основой исследования стали диалектический, исторический, анализа и синтеза, структурно-функциональный, классификации и группировки, логико-семантический, сравнительно-правовой, герменевтический методы. Целью данной статьи является исследование понятия и сущности правовой концепции ресоциализации, исследование средств исправления и ресоциализации осужденных, анализ опыта зарубежных стран в сфере ресоциализации осужденных, анализ приоритетных направлений украинской социальной политики по ресоциализации лиц, а также наметка путей улучшения состояния ресоциализации осужденных в Украине.

The correction and resocialization of the convicted person are considered processes of positive changes that occur in his most personality and create readiness for self-directed obedient behavior, as well as the return of the convicted person to an independent and generally accepted social and normative life in society, that is, the successful reintegration into society after release and deprivation of a criminal worldview. This remains one of the most important issues debated by scholars to determine the best way to achieve the goals of corrections and rehabilitation of ex-offenders. In addition, resocialization is of fundamental importance for solving a wide range of social and socio-practical problems, not only for the prevention and eradication of crime but also for the prevention of social deviance in general. Since the reintegration of criminals into society is an urgent social problem, a detailed analysis of the process of resocialization of criminals is of practical importance. The methodological basis of the research was the dialectical, historical, analysis and synthesis, structural-functional, classification and grouping, logical-semantic, comparative-legal, and hermeneutic methods. The purpose of this article is the study of the concept and essence of the legal concept of resocialization, the study of the means of correction and resocialization of convicted persons, the analysis of the experience of foreign countries in the field of resocialization of convicts, the analysis of the priority directions of the Ukrainian social policy on resocialization of persons, and the outline of the ways to improve the state of resocialization of convicted persons in Ukraine.

Під виправленням і ресоціалізацією засудженого розуміють процеси позитивних змін, які відбуваються в його особистості та формують готовність до самостійної слухняної поведінки, а також повернення засудженого до самостійного і загальноприйнятого соціально-нормативного життя в суспільства, тобто успішна реінтеграція в суспільство після звільнення і позбавлення кримінального світогляду. Це залишається одним із найважливіших питань, яке обговорюється вченими для визначення найкращого способу досягнення цілей виправлення та реабілітації колишніх правопорушників. Крім того, ресоціалізація має принципове значення для вирішення широкого кола соціальних і соціально-практичних проблем не тільки для попередження та викорінення злочинності, але й для профілактики соціальних девіацій в цілому. Оскільки реінтеграція злочинців у суспільство є актуальною соціальною проблемою, практичне значення має детальний аналіз процесу ресоціалізації злочинців. Методологічну основу дослідження склали діалектичний, історичний, аналізу та синтезу, структурно-функціональний, класифікаційно-групувальний, логіко-семантичний, порівняльно-правовий та герменевтичний методи. Метою даної статті є дослідження поняття та сутності правового поняття ресоціалізації, дослідження засобів виправлення та ресоціалізації засуджених, аналіз досвіду зарубіжних країн у сфері ресоціалізації засуджених, аналіз пріоритетних напрямів соціальної політики України щодо ресоціалізації осіб та окреслення шляхів покращення стану ресоціалізації засуджених в Україні.
Keywords: publikatsii u WoS; Ukraine; penitentiary system; resocialization; social adaptation; social rehabilitation; reintegration; Україна; пенітенціарна система; ресоціалізація; соціальна адаптація; соціальна реабілітація; реінтеграція; Украина; пенитенциарная система; ресоциализация; социальная адаптация; социальная реабилитация; реинтеграция